REVIEW OF INTERNATIONAL SPORTS COMPETITIONS AND SIGNIFICANT SPORTS BUILDINGS IN UKRAINE - Votinov, М.; Smirnova, О. (Municipal economy of cities. Series: «Economy science», 2023)
The article is devoted to the review of international sports competitions. The article is devoted the research of the peculiarities of the formation and functioning of sports facilities in Ukraine. The conceptual apparatus of the research has been studied. It was determined that modern sports complexes are a set of sports facilities of universal purpose, the construction of which is carried out according to a single project documentation. It has been established that they are large-scale structures, which are distinguished by originality and non-standard constructions and forms, in which complex design, technical and engineering solutions are implemented. The complex also includes outdoor playgrounds, athletics playgrounds, and outdoor water sports objects. Such buildings and complexes are intended for holding various sports events. An analysis of the domestic experience of the formation of sports buildings and complexes in the urban environment was carried out. The main international sports competitions are considered. The coverage of the main sports events and the analysis of the formation of significant sports facilities in Ukraine made it possible to determine that the modern stage is characterized by the active implementation of multi-functionality and transformation methods, universality and saturation of sports facilities with engineering infrastructure and high-tech elements. The peculiarities and directions of the formation of sports objects in Ukraine are revealed. Specificity, methods of formation of modern sports complexes are determined. Based on the analysis of the formation of domestic sports objects, the main modern requirements for their improvement have been determined. A number of modern requirements for improving the methods of operating sports facilities and complexes and increasing the efficiency of their use have been determined. The algorithm of the conceptual approach to the improvement of sports facilities and complexes in the structure of the urban environment is revealed.